2001
DOI: 10.1046/j.1198-743x.2001.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence microdiversity at the ribosomal RNA operons of Escherichia coli pyelonephritogenic strains

Abstract: UAP and non-obstructive CAP E. coli strains are sensitive to antimicrobials, show a high level of the pap gene and belong to the selective, homogeneous and highly protected molecular alpha2 group, where no recombinations, deletions or insertions are present. On the contrary, obstructive and vesicorenal reflux E. coli strains show significant antimicrobial resistance, high intercistronic heterogenicity (wide presence of block nucleotidic substitutions, deletions or insertions) and significantly lower virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It could be hypothesized that presence and nature of secondary structures within the target regions as well as the GC ratios of the resultant fragments may have contributed to the differences. It is known that the V1, V4 and V7 regions exhibit differences in the number of stems as well as in nucleotide variations within these stems [38], [39], and while is possible that differential amplification efficiencies contributed to the compositional differences, it is not within the scope of this study to test this hypothesis. It has been shown that higher GC ratios result in higher amplification efficiencies [35], thereby altering PCR kinetics, with over-amplification of rare members and under-representation of dominant species [40].…”
Section: Discussionmentioning
confidence: 95%
“…It could be hypothesized that presence and nature of secondary structures within the target regions as well as the GC ratios of the resultant fragments may have contributed to the differences. It is known that the V1, V4 and V7 regions exhibit differences in the number of stems as well as in nucleotide variations within these stems [38], [39], and while is possible that differential amplification efficiencies contributed to the compositional differences, it is not within the scope of this study to test this hypothesis. It has been shown that higher GC ratios result in higher amplification efficiencies [35], thereby altering PCR kinetics, with over-amplification of rare members and under-representation of dominant species [40].…”
Section: Discussionmentioning
confidence: 95%
“…Amplified ribosomal restriction analysis (ARDRA) was performed on the DNA preparations by the method described by Anton et al (2). The analysis is based on variations of the 16S-23S rRNA intergenic spacer region (ISR) sequence and has been reported to be useful for revealing phylogenic divergence within E. coli (3). Briefly, PCR amplification targeting a partial sequence of the rrn genes including the 16S-23S ISR was performed using a DNA thermal cycler (GeneAmp PCR System 2700; Applied Biosystems) with a set of primers, univ-f (5'-GAGTTTGATCCTGGCTCA-3'; sense primer) and univ-r (5'-CCGGTCCTCTCGTACT-3'; anti-sense primer).…”
mentioning
confidence: 99%